Substitute of Expensive Pt with Improved Electrocatalytic Performance and Higher Resistance to CO Poisoning for Methanol Oxidation: the Case of Synergistic Pt-Co3O4 Nanocomposite - Zhao, Hongxiao; Zheng, Zhi; Li, Jing; Jia, Huimin; Wong, Ka-wai; Zhang, Yidong; Lau, WoonMing (Nano-Micro Letters, 2013)
In this paper, Pt-Co3O4 nanocomposite was synthesized by a sol-gel process combined with electrodeposition method. Its electrocatalytic activity towards methanol oxidation was investigated at room temperature using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and current density-time curve. It is found that the resultant Pt-Co3O4 catalysts with minute amount of Pt exhibite attractive electrocatalytic activity for methanol oxidation reaction (MOR) but with a high resistance CO poisoning due to the synergistic effects from Pt and Co3O4. Together with the low manufacturing cost of Co3O4, the reported nanostructured Pt-Co3O4 catalyst is expected to be a promising electrode material for direct methanol fuel cells (DMFC).